2020
DOI: 10.3390/catal10080898
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Pt-Sn/Al2O3 Catalyst for Hydrogen Production through Propane Dehydrogenation Using Hydrochloric Acid

Abstract: Compared with dehydrogenation in conventional petroleum refinery processes, relatively pure hydrogen can be produced by propane dehydrogenation (PDH) without innate contaminants like sulfur and metals. Among the existing catalysts for PDH, Pt catalysts are popular and are often used in conjunction with Sn as a co-catalyst. Coke formation is a major concern in PDH, where catalyst regeneration is typically achieved by periodic coke burning to achieve sustainable operation. In this study, Pt-Sn/Al2O3 catalysts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Although the conversion decreased, the calculated TOF for propane conversion (shown in Table 1) on these catalysts actually increased. During the oxidation treatment, surface chlorine species and hydroxyl groups are partly removed from the support surface and the sites for anchoring Pt and/or Sn species also change 28 and, therefore, the structural properties and catalytic performance change as well. From the characterization results stated above, it's found that the multiple Pt–Pt sites and the Pt species with a weak interaction with the carrier diminish due to the mobility of the Pt and/or Sn species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the conversion decreased, the calculated TOF for propane conversion (shown in Table 1) on these catalysts actually increased. During the oxidation treatment, surface chlorine species and hydroxyl groups are partly removed from the support surface and the sites for anchoring Pt and/or Sn species also change 28 and, therefore, the structural properties and catalytic performance change as well. From the characterization results stated above, it's found that the multiple Pt–Pt sites and the Pt species with a weak interaction with the carrier diminish due to the mobility of the Pt and/or Sn species.…”
Section: Resultsmentioning
confidence: 99%
“…During the oxidation treatment, surface chlorine species and hydroxyl groups are partly removed from the support surface and the sites for anchoring Pt and/or Sn species also change 28 and, therefore, the structural properties and catalytic performance change as well. From the characterization results stated above, it's found that the multiple Pt-Pt sites and the Pt species with a weak…”
Section: Catalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Coke burning may result in extensive active metal sintering, so alternative regeneration processes have also been proposed, which make use of ozone, hydrogen and oxychlorination. Optimal conversion recovery has been obtained by treatment of Pt-Sn/Al 2 O 3 catalysts, with 35% HCl, after coke burning [98]. HCl treatment seems to play a similar role as oxychlorination in redispersing the Pt particles and generating the Pt 3 Sn alloy.…”
Section: Catalyst Regeneration and Coke Combustion Kineticsmentioning
confidence: 98%
“…The measured values for the conversions, signal enhancement factors, and pairwise selectivities of three NPs after the oxidation–reduction cycling are summarized in Figure S6 and Table S7. The restoration in the performance of three NPs is likely due to the removal of surface carbon deposits during the catalyst regeneration process. Thus, Pt 3 Sn@mSiO 2 and PtSn@mSiO 2 iNPs are robust and effective catalysts for achieving high NMR signal enhancement with excellent durability and recyclability in parahydrogen enhanced NMR. For these catalysts, the mSiO 2 shell effectively prevents the encapsulated iNPs from aggregation at high temperatures.…”
mentioning
confidence: 99%